Management Culture and Corporate Social Responsibility - ?ukauskas, Pranas; Vveinhardt, Jolita; Andriukaitien?, Regina (IntechOpen, 2018)
This monograph focuses on the level of management culture development in organizations attempting to disclose it not only with the help of theoretical insights but also by the approach based on employees and managers. Why was the term "management culture" that is rarely found in literature selected for the analysis? We are quite often faced with problems of terminology. Especially, it often happens in the translation from one language to another. While preparing this monograph, the authors had a number of questions on how to decouple the management culture from organization's culture and from organizational culture, how to separate management culture from managerial culture, etc. However, having analysed a variety of scientific research, it appeared that there is no need to break down the mentioned cultures because they still overlap. Therefore, it is impossible to completely separate the management culture from the formal or informal part of organizational culture. Management culture inevitably exists in every organization, only its level of development may vary.